Design and Build Daily Android-Based Financial Applications - Susi Susilowati; Abdul Rohmat Sigit (IJISTECH (International Journal of Information System and Technology), 2020)
The rapid development of information and communication technology is directly proportional to the community's need for fast and accurate information, especially the development of technology on mobile phones (cellphones) that present smartphones with various sophisticated features. Smartphones are becoming a necessity for society today not only as a communication device, but also as a source of information. In general, the community carries out daily financial management in the traditional way by taking notes using a writing instrument, where the paper media as its documentation and the help of a calculating tool is a calculator to calculate financial income and expenditure. Constraints that occur are that the public needs stationery to do every recording of transactions that are carried out every day. So it requires quite a lot of money, the time required will take a long time to record financial transactions that are carried out every day by the process of writing on paper media, in addition to that the public is also often confused by financial records that are lost or damaged due to paper documents. This Mobile Based Daily Financial Registration Application aims to help its users in financial management using a mobile device, so that users can expect to be able to manage their finances optimally, both income and expenditure. As a result of the application, the public can enter the daily money in and daily money out data along with their information and then the data will be displayed on the front page of the application menu, in addition to the data that has been entered can also be edited and deleted as needed and accompanied by making features money entry data reports and money out data in the form of graphs and pdfs.